Infection of Parainfluenza type 3 (PI-3) as one of the causative agent of pneumonia in sheep and goats - Sendow, Indrawati; Syafriati, Tatty; Wiedosari, Ening; Selleck, Paul (Indonesian Animal Sciences Society, 2002)
Serological survey was conducted to obtain the prevalence of Parainfluenza type 3 (PI-3) reactor as one of the causative agent of pneumonia in sheep and goats in abatoir at Jakarta and some small holder farms in Indonesia. Serological test using serum neutralization from 724 goat sera and 109 sheep sera indicated that only 1% of goats were serologically reactors and none of sheep sera had antibodies against PI-3 virus. Isolation of the virus from 56 bronchus and trachea swab and 345 lungs indicated that only one sampel from lung showed cythopathic effect (CPE) in Madin Darby Bovine Kidney (MDBK) cell lines identification of the virus using serum neutralization test indicated that the virus neutralized reference PI-3 antisera. The isolate came from one lung (7%) of 24 that showed histopathologically pneumonia intertitialis that usually caused by viral infection. Key words: Parainfluenza type 3 (PI-3), virus isolation, sheep, goat, pneumonia intertisialis